Pengaruh Gaya Kepemimpinan Dan Evaluasi Kinerja Karyawan Di PT. Shopee Indonesia - Dhea Indah Kusumawardani; Sri Sundari; Marisi Pakpahan (Lokawati : Jurnal Penelitian Manajemen dan Inovasi Riset, 2024)
This research aims to analyze the influence of leadership style and performance evaluation on employees at PT. Shopee Indonesia with a qualitative approach. The research method uses analysis of documents, articles, websites and journals related to leadership policies and employee performance evaluation. Leadership style, especially transformational, has a significant positive influence on employee motivation and performance at PT. Shopee Indonesia. Performance evaluation has also been shown to play a role in shaping employee perceptions of recognition for their contributions. This provides insight for company management in optimizing leadership practices and performance evaluation systems to improve work quality and employee productivity.